AGEN CERDAS PEMBELAJARAN ILMU TAJWID UNTUK SISWA KELAS VII STUDI KASUS (MTs. NURUL FALAH CIATER) - Nining Suryani (Paradigma, 2014)
Learning is defined as the process of creating an environment that allows the learning process. Multimedia learning can be defined as a multimedia application that is used in the learning process. In general, the benefits that can be obtained from a multimedia learning is the learning process more interesting, more interactive, the amount of teaching time can be reduced , the quality of children's learning can be improved and the process of teaching and learning can be done anywhere and at any time, as well as the attitude of children's learning can be improved. Learning on students Mts Nurul Falah Ciater still using conventional methods , where the process of learning and teaching face-to- face with makeshift props. This is a constraint of which is the students feel interested in the subjects given tajwid especially in learning, students are less able to understand the science of recitation so the other required instructional media that can make learning more interesting atmosphere so that students can easily understand tajwid learned . One of them is especially multimedia instructional media with interactive multimedia. With the medium of interactive multimedia learning and teaching process is expected to be optimal and conducive and students can more quickly read the Quran with proper recitation. Key Word : Interactive Animation, intelligent agents